2004
DOI: 10.1105/tpc.021154
|View full text |Cite
|
Sign up to set email alerts
|

NAI1 Gene Encodes a Basic-Helix-Loop-Helix–Type Putative Transcription Factor That Regulates the Formation of an Endoplasmic Reticulum–Derived Structure, the ER Body

Abstract: Plant cells develop various types of endoplasmic reticulum (ER)-derived structures with specific functions. ER body, an ERderived compartment in Arabidopsis thaliana, is a spindle-shaped structure. The NAI1 gene regulates the development of ER bodies because mutation of NAI1 abolishes the formation of ER bodies. To better understand the role of NAI1, we cloned the NAI1 gene using a positional cloning strategy. The nai1-1 mutant had a single nucleotide change at an intron acceptor site of At2g22770 (NAI1 gene).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
108
0
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(118 citation statements)
references
References 86 publications
2
108
0
8
Order By: Relevance
“…Indeed, PBP1 contributes to PYK10 activity and may act as a molecular chaperone that facilitates the correct polymerization of PYK10 when cells are exposed to stress. The PYK10 and PBP1 genes are both regulated by the NAI1 (At2g22770) basic-helix-loop-helix-type transcription factor (105). Moreover, it has also been demonstrated that NAI2 (At3g15950) deficiency in Arabidopsis specifically reduces the accumulation of PYK10 protein but does not affect the accumulation of PBP1 (111).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Indeed, PBP1 contributes to PYK10 activity and may act as a molecular chaperone that facilitates the correct polymerization of PYK10 when cells are exposed to stress. The PYK10 and PBP1 genes are both regulated by the NAI1 (At2g22770) basic-helix-loop-helix-type transcription factor (105). Moreover, it has also been demonstrated that NAI2 (At3g15950) deficiency in Arabidopsis specifically reduces the accumulation of PYK10 protein but does not affect the accumulation of PBP1 (111).…”
Section: Discussionmentioning
confidence: 97%
“…The Arabidopsis PYK10 protein (At3g09260) was described as a root-and hypocotyl-specific myrosinase (104) whose activity could release glucose and breakdown products, including defense compounds such as isothiocyanates. To date, the physiological role and natural substrate(s) of PYK10 are unknown, but functional ␤-glucosidase and ␤-fucosidase activities have been reported for PYK10 (105). In addition, nitrile-specifier protein 2 is abundant in both dry and germinating Arabidopsis seeds and is also progressively translated (supplemental Tables S1 and S7).…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have used GFP-based screens to isolate Arabidopsis mutants that have abnormally shaped organelles, including mitochondria (Logan et al, 2003), peroxisomes (Mano et al, 2004), vacuolar membranes (Avila et al, 2003), and ER bodies (Matsushima et al, 2003(Matsushima et al, , 2004. Thus, GFP screening is a useful method for studying organelle morphology and biogenesis.…”
Section: Transgenic Arabidopsis Gfp-2sc Plants Are An Ideal Tool For mentioning
confidence: 99%
“…Arabidopsis plants (1 to 3 weeks old) were transformed with each chimeric gene by particle bombardment as described previously (Matsushima et al, 2004). To generate transgenic Arabidopsis plants, we transformed kam1-1 with a chimeric gene encoding KAM1-mRFP by the in planta method (Bechtold and Pelletier, 1998).…”
Section: Transient and Stable Expression In Arabidopsismentioning
confidence: 99%
“…S5). In Arabidopsis, a bHLHm1 homolog, At2g22770 (NAI1), is involved in stress-induced synthesis of ER bodies in root and leaf tissues (42). It is possible that bHLHm1 TFs may have a role in facilitating other microbial interactions, including pathogen responses or mycorrhizal symbioses, both of which involve C supply from the plant.…”
Section: Discussionmentioning
confidence: 99%